Texture profile and correlation between sensory and instrumental analyses on extruded snacks - Paula, Amanda Maldo [UNESP]; Conti-Silva, Ana Carolina [UNESP] (Elsevier, 2014)
Instrumental texture analysis on extruded snacks is widely applied, however there is no scientific consensus about the test and probe types that can be correlated with the sensory texture of snacks. Eleven commercial extruded snacks of different shapes were evaluated instrumentally using different probes and sensorially through descriptive analysis. The snack texture was described using the attributes of hardness, crispness, adhesiveness, fracturability and chewiness. Cylindrical snacks were described through crispness and fracturability, pelleted and shell-shaped snacks by chewiness and ring-shaped snacks by adhesiveness and hardness. Hardness and adhesiveness were correlated with a Warner-Bratzler test using a V shape probe (r = 0.718 and r = 0.763, respectively), while fracturability and chewiness were correlated with a Warner-Bratzler test using a guillotine (r = 0.776 and r = 0.662, respectively). The fairly strong good correlations enable application of these instrumental tests as an indication of the sensory texture of extruded snacks. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Descriptive analysis; Instrumental analysis; Snack food; Texture; Different shapes; Extruded snacks; Good correlations; Instrumental texture analysis; Texture profile; Hardness; Instruments; Pelletizing; Probes; Textures